أثر السياسات النقدية على القيمة الشرائية لليرة السورية (2001-2013) (Latakia University Journal - Economic and Legal Sciences Series, 2017)
تهدف هذه الدراسة إلى التعرف على أثر السياسات النقدية المتبعة من قبل مصرف سورية المركزي على القيمة الشرائية لليرة السورية، و ذلك وفق أسس علمية تقوم على قراءة واقع الاقتصاد السوري، والسياسات والإجراءات المقابلة لهذا الواقع، ومن أجل ذلك تم الاعتماد على الجداول والمنحنيات والتحليل الاقتصادي، و على مدى أثر تلك السياسات على الشرائح الاجتماعية محدودة الدخل، وخاصة في مرحلة الأزمة الراهنة، نظراً لانخفاض سعر صرف الليرة السورية مقابل العملات الأجنبية، وارتفاع معدل التضخم بشكل غير مسبوق، بالإضافة إلى دارسة أثر المتغيرات الاقتصادية التي تؤثر على قيمة الليرة السورية، والتي تكون خارج سيطرة مصرف سورية المركزي.وتوصلت الدراسة إلى أن العامل الذاتي لم يكن بالمستوى المطلوب لاحتواء العامل الموضوعي، أي إن السياسات والإجراءات لم تكن بالمستوى المطلوب، أو كانت مقتصرة على أداة واحدة من أدوات السياسة النقدية تمثلت بـسعر الصرف، و من ثم لم تعمل على تحقيق الاستقرار في قيمة العملة الوطنية و في استقرار الأسعار، و هما الهدف النهائي للسياسة النقدية لدى مصرف سورية المركزي.This research aims to identify the impact of monetary policies adopted by the Central Bank of Syria on the purchasing value of the Syrian pound. According to scientific principles based on reading the reality of the Syrian economy, and the corresponding policies and procedures to this fact, and for this reason the study depended on the tables and curves and economic analysis and also the extent of the impact of those policies on low-income social strata. Especially in the current crisis due to the low exchange rate of the Syrian pound against foreign currencies and high inflation rate in an unprecedented way. In addition to the study of the impact the economical changes which affect the value of the Syrian pound that could be out of control of the Central Bank of Syria . the study found the subjective factor was not at the level required to contain the objective factor, that is, those policies and procedures were not at the required level, or were limited to one tool of monetary policy tools and therefore did not work to stabilize the national currency, and thus prices stability, that is the ultimate purpose of monetary policy at the Central Bank of Syria.